Chronic Suppurative Otitis Media: A Case Report - Yazdi, M.M. K.; Ghalavand, Zohreh; Yazdi, Alireza K.; Kodori, Mansoor; Taheri, Marzieh; Tabriz, Mahboobeh S.; Eslami, Gita (Infectious Disorders - Drug Targets, 2020)
Background Context: Chronic Suppurative Otitis Media (CSOM) is a common cause of hearing impairment and disability. CSOM caused by Pseudomonas aeruginosa is usually treated with topical ciprofloxacin and resistance to ciprofloxacin in CSOM isolates has rarely been reported. Case Presentation: A 24-year-old male patient with CSOM due to p. aeruginosa was reported. CSOM was prolonged for ten years and physician prescribed topical ciprofloxacin drops, pus suctioning and ear pH alteration. The treatment wasn’t effective and the patient came back to the clinic with relapse of suppurative otitis media. P. aeruginosa was isolated as the cause of CSOM and the isolate was resistant to ciprofloxacin, aztreonam, imipenem, gentamicin, doripenem, cefepime, levofloxacin, amikacin and susceptible to colistin and ceftazidime. There were two mutations in gyrA and eight mutations were observed in nfxB genes. Finally, tympanomastoidectomy was done. Conclusion: Usually topical antibiotics, especially ciprofloxacin, is effective against ear infections but our case was different and the P. aeruginosa isolated from CSOM was resistant to most of the antibiotics. One reason for CSOM recurrence might be surgery failure. The routine and primary treatment for CSOM did not seem sufficient and tympanomastoidectomy is suggested to be the best treatment approach for these patients.
Keywords: chronic